State-of-the-Art Labs: Inside UiTM's versatile pharmaceutical pharmacology and chemistry laboratories / Tiniati Ahmad and Associate Prof. Dr. Mahmathi Karuppannan - Ahmad, Tiniati; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
Department of Pharmaceutical Pharmacology and Chemistry conducts studies on drug structure and synthesis of biologically active molecules. The labs are utilised for both teaching and research purposes. Pharmaceutical Chemistry Laboratories under this department are located at Level 8, FF3 Building. The labs provide well-maintained equipment and facilities for teaching and research purposes for undergraduates, postgraduates, and researchers from UiTM as well as other government and private organisations. The courses provided by the department include Fundamentals of Pharmaceutical Chemistry (PHC 414), Pharmacognosy (PHC 614), Pharmaceutical Organic Chemistry (PHC 464), and Pharmaceutical Analysis (PHC 563). There are various types of laboratory equipment but the main ones for servicing are the Rotary Evaporator and UV-Vis Spectroscopy. A rotary evaporator is mainly used for evaporation, concentration, crystallisation, drying, separation, and solvent recovery, as well as the continuous distillation of large amounts of volatile solvents under reduced pressure. It can be utilized in pilot experiments and productions in the biological, pharmaceutical, chemical and food processing industries.